A new non-polynomial four variable shear deformation theory in axiomatic formulation for hygro-thermo-mechanical analysis of laminated composite plates. (15th December 2017) - Joshan, Y.S.; Grover, Neeraj; Singh, B.N.
Abstract: In the present work, a new non-polynomial shear deformation theory having four variables is developed and assessed for hygro-thermo-mechanical response of laminated composite plates. An inverse hyperbolic function of thickness coordinate is used in the displacement field in order to consider the shear deformation effects. The principle of virtual work is used to derive the governing equations which are resolved for cross-ply plates in axiomatic approach. Navier type closed form solution is used to solve the governing equations for simply supported boundary conditions. The non-dimensional results for transverse deflection and stresses are validated with the existing results. A variety of examples are considered for different loading conditions, lamination, material properties etc. in order to evaluate the capability of the present modal. It is observed from the results that the present modal efficiently predicts the bending response of laminated plates in hygro-thermal environment at lesser computational cost.